The effectiveness of the problem-based learning method by using Song Lyrics to improve students’ speaking skills - Gumelar, Wahyu Satya; Apriani, Nur Shintia; Rina, Neng (EduLite: Journal of English Education, Literature and Culture, 2024)
Speaking is one of the skills that students must have be able to communicate confidently, exchange ideas or ideas, collect information, and share information with others. However, students now have a lot of difficulties when speaking or just saying words in English. Because they are afraid of making mistakes in pronouncing good vocabulary. Even though speaking is a goal that must be achieved in learning English. One suitable solution is the problem-based learning approach, which allows students to participate actively in their learning, share ideas, and boost their self-confidence. This study aims to find out whether the problem-based learning method (PBL) with the use of song lyrics in learning can improve students' understanding of speaking skills. This research was conducted using a quasi-exsperimental quantitative method. This research involved 30 students in grades XI-1 and 30 students in grades XI-3 of SMA Karya Pembangunan Cicalengka. Students will be placed in two classes, namely the experimental group and the control group. The class begins with a Pre-test, and the Post-test is carried out at the last meeting after the treatment. The researcher obtained data from the results of the pre-test and post-test of students. From the data analysis, the scores in the experimental group and the control group increased. However the improvement in the experimental group was better than in the control group. In the experimental group, the average pre-test score was 57.9, and the post-test score was 75.6. The control group's pre-test average was 54.86, and the post-test was 66.53. The data showed that the experimental group's post-test average (75.6) was higher than the control group's (66.53), supporting the hypothesis that problem-based learning with song lyrics improves students' speaking skills.